(untitled) (The International Journal of Educational Sciences and Arts, 2025)
This study aims to explore the effectiveness of generative artificial intelligence applications in developing presentation design skills and digital awareness among primary school teachers. The study highlights the importance of artificial intelligence as a supportive tool in designing interactive and engaging presentations, as well as in facilitating the process of text analysis and automatic slide creation. The study adopted a procedural approach with a quasi-experimental design and included a sample of 20 primary school teachers. Tools such as a digital awareness questionnaire and an electronic content evaluation card were used to assess the presentations. The results indicate that these applications provide a variety of tools for creating presentations, including text analysis, automatic slide generation, recommendations for layout and design, simplification of data presentation, and making the presentations more accessible, attractive, and clear. The study shows that the educational design followed was effective in developing presentation design skills, encompassing steps of analysis, design, development, implementation, and evaluation. This led to a significant improvement in the quality of the presentations in terms of design, organization, and content. Despite the positive results in developing presentation skills, the study did not show a statistically significant effect of artificial intelligence applications on the development of digital awareness among teachers, indicating the need for further research in this area. The findings support the use of generative artificial intelligence applications in education to enhance presentation design skills and highlight the importance of developing specialized training programs, to effectively develop digital awareness.